'Grab, ride and go': an investigation into the use of ride-hailing services in a developing economy. (23rd March 2021) - Choong, Cheng-Leng; Goh, Yen-Nee
The purpose of this study is to investigate the factors that influence the intention to use ride-hailing applications in Malaysia. We use a research model that integrates the technology acceptance model (TAM) and the theory of planned behaviour (TPB), which includes perceived risk constructs. Data were collected via a survey of 392 smartphone users in Malaysia. Our findings reveal that perceived ease of use, attitude towards ride-hailing applications, subjective norms and perceived behavioural control are significant predictors of the intention to use ride-hailing applications. The integration of TAM and TPB provides good explanatory power for the intention to use ride-hailing applications. Theoretical and practical implications are discussed.